The Empty House Next Door : Understanding and Reducing Vacancy and Hypervacancy in the United States - Mallach, Alan (Lincoln Institute of Land Policy, 2018)
Renowned city planner and housing advocate Alan Mallach presents effective strategiesfor community leaders, local officials, and nonprofits contending with vacant propertiesin the United States. Examples illustrate creative ways to reduce the harm caused byvacant properties, jump-start housing markets in struggling neighborhoods, create thepotential for future revival, and transform vacant properties into community assets.